2018
DOI: 10.1002/jcp.27134
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of the transient receptor potential melastatin 2 channel in a positive feedback mechanism for reactive oxygen species‐induced delayed cell death

Abstract: Transient receptor potential melastatin 2 (TRPM2) channel activation by reactive oxygen species (ROS) plays a critical role in delayed neuronal cell death, responsible for postischemia brain damage via altering intracellular Zn homeostasis, but a mechanistic understanding is still lacking. Here, we showed that H O induced neuroblastoma SH-SY5Y cell death with a significant delay, dependently of the TRPM2 channel and increased [Zn ] , and therefore used this cell model to investigate the mechanisms underlying R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…Synaptically released zinc after GCI stimulates protein kinase C (PKC), and PKC contributes NADPH oxidase activation [ 65 ]. (3) A major activator of TRPM2 is ADP-ribose (ADPR), which is released upon oxidative stress including ROS [ 66 , 67 ]. (4) ROS-induced TRPM2 activation triggers increased secondary zinc influx [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Synaptically released zinc after GCI stimulates protein kinase C (PKC), and PKC contributes NADPH oxidase activation [ 65 ]. (3) A major activator of TRPM2 is ADP-ribose (ADPR), which is released upon oxidative stress including ROS [ 66 , 67 ]. (4) ROS-induced TRPM2 activation triggers increased secondary zinc influx [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, the activity of nuclear PARP, particularly PARP-1, is crucial for the induction of ADPR generation and subsequent TRPM2 channel activation by ROS and other OS-inducing pathological stimuli. PARP inhibitors have been used in many studies as an alternative or additional means to prevent OS-induced TRPM2-mediated effects [ 36 , 39 , 48 , 74 , 75 , 82 , [121] , [122] , [123] , [124] , [125] , [126] ], including cell death. Example PARP inhibitors include SB-750139, N-(6-oxo-5,6-dihydro-phenanthridin-2-yl)-N,N-dimethylacetamide (PJ34), 3-aminobenzamide (3-AB) and 3,4-dihydro-5-[4-(1-piperidinyl)butoxy]-1(2H)-isoquinolinone (DPQ).…”
Section: Trpm2 Channel Properties Activation Mechanisms and Pharmacmentioning
confidence: 99%
“…These results support the notion that reperfusion-induced TRPM2 channel activation alters intracellular Zn 2+ homeostasis that triggers delayed neuronal cell death [ 40 ]. As described above in an early study showing H 2 O 2 -induced TRPM2-mediated delayed neuronal cell death in cultured mouse hippocampal neurons [ 135 ], our recent study has shown that H 2 O 2 can induce similar delayed cell death in SH-SY5Y cells, with PI staining detecting negligible cell death immediately after exposure to H 2 O 2 (100–300 μM for 2 h) but substantial cell death after cells were cultured in normal and H 2 O 2 ‐free medium for a further 24 h [ 124 ]. H 2 O 2 ‐induced delayed cell death in SH-SY5Y cells was also mitigated by treatment with PJ34, DPQ, 2-APB or ACA, and by removal of extracellular Ca 2+ , suggesting a critical role for PARP-dependent TRPM2 channel activation and subsequent TRPM2-mediated Ca 2+ signalling in such delayed cell death.…”
Section: Trpm2 In Neuronal Cell Death Associated With Ischemia/reperfmentioning
confidence: 99%
“…61 In a recent study examining human SH-SY5Y neuroblastoma cells, we have shown that H 2 O 2 induced neuronal cell death with a significant delay, requiring the TRPM2 channel activation and TRPM2-dependent increase in the [Zn 2+ ] i . 73 We have further used such a neuronal cell model to gather strong evidence to suggest that ROS-induced activation of the TRPM2 channel sets in motion a vicious positive feedback signalling mechanism for delayed neuronal death ( Figure 2B). 73…”
Section: Cellul Ar and Molecul Ar Mechanis Ms Mediating B R Ain Dammentioning
confidence: 99%
“…73 We have further used such a neuronal cell model to gather strong evidence to suggest that ROS-induced activation of the TRPM2 channel sets in motion a vicious positive feedback signalling mechanism for delayed neuronal death ( Figure 2B). 73…”
Section: Cellul Ar and Molecul Ar Mechanis Ms Mediating B R Ain Dammentioning
confidence: 99%